IMPROVING THE SHOVELS OF THE DRUM DRYER OF THE COTTON PROCESSING PLANT TO INCREASE THE VIBRATION LEVEL OF COTTON (Journal of Science-Innovative Research in Uzbekistan, 2024)
In the article, instead of the shovels in the inner part of the drum, concave-shaped shovels were installed, and in the middle of the concave-shaped shovels, 150 mm high, 18 mm diameter stakes made of wire (prut) were installed. As a result, it is possible to throw the cotton into the useless zone of the inner chamber of the drying drum, and to dry the seeded cotton evenly over the entire surface of the drum. Throwing the cotton in the useless zone and ripping it, in turn, allows accelerating the release of moisture in the seeded cotton and makes it possible to efficiently use the heat of the hot air supplied to the drum